Towards Robust Internal Control: Insights from Quality and Security of Information Systems - Harsono, Khaerunisa; Putra, Vicky Dzaky Cahaya (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Banks are one of the companies that use computers as a means of information systems. Internal control is used to prevent the possibility of inefficiency, error, and embezzlement of assets. So it is necessary to have a strict information and security system, the quality of the accounting information system and its security is very important for effective internal control to overcome possible errors. This study aims to determine the partial and simultaneous influence between the quality of accounting information systems and the security of accounting information systems on the company's internal control at BJB Purwakarta Sub-Branch Office. This study uses qualitative research and data collection techniques through distributing questionnaires, the analysis used includes, classical assumption test, multiple linear regression analysis test and hypothesis testing using SPSS. Based on the research results, the t test results show that the quality of the accounting information system has no effect on the company's internal control and the security of the accounting information system affects internal control. While the results of the f test show that the accounting information system and the security of the accounting information system affect internal control.